The Political Economy of the Prussian Three-Class Franchise - Sascha O. Becker; Erik Hornung (Center for Economic Studies and ifo Institute (CESifo), 2019)
Did the Prussian three-class franchise, which politically over-represented the economic elite, affect policy-making? Combining MP-level political orientation, derived from all roll call votes in the Prussian parliament (1867–1903), with constituency characteristics, we analyze how local vote inequality, determined by tax payments, affected policymaking during Prussia's period of rapid industrialization. Contrary to the predominant view that the franchise system produced a conservative parliament, higher vote inequality is associated with more liberal voting, especially in regions with large-scale industry. We argue that industrialists preferred self-serving liberal policies and were able to coordinate on suitable MPs when vote inequality was high.
Keywords: D72; N43; N93; P26; 330; inequality; political economy; three-class franchise; elites; Prussia